La femme et le développement au Maghreb. Une approche socio-culturelle - Hachlouf, Brahim (Afrika Focus, 1991)
The under-development problem of the Third World can not exclusively be attributed to economic backlogging, political crises or supernatural events. The perseverance of old ancestral values, cultural, social and psychological, still remain obstructions to any social evolution in a country. The woman's role in society in these countries, is restricted to house-keeping and the bearing of children. A situation which weighs heavy on their economies. This article will shed light on the essential elements which hinder active woman participation in development of their economies, in particular in the Maghreb- countries. Discussed is their personal status, women's position in education and in the work-force. KEY WORDS: development, emancipation, islam, Maghreb, woman